Holin-esteraze - Stojan, Rok (Medicinski razgledi, 2008)
Cholinesterases are involved in terminating nerve impulses in the central nervous system and at the periphery. The high enzyme concentration at the cholinergic synapses is achieved by oligomerization on an anchoring, collagen-like peptide. The 3D structure of a monomer shows a buried active site, which is responsible for the effectiveness and specificity of the enzyme, but also for various pseudocooperative phenomena. Due to its importantrole, acetylcholinesterase is a target for various inhibitors, natural as well as artificial ones. Reversible inhibitors prevent substrate accommodation by stericaily blocking the active site and the irreversible onesact as acylating agents that modify the active site serine, the major participant in covalent catalysis. When irreversibly inhibited by potent nervegases, cholinesterases can be reactivated, unless partial dealkylation ofthe bound inhibitor has occurred. This particular phenomenon, called aging of cholinesterases, along with generalized cytotoxic effect appear to be the cause of organophosphate-induced delayed neurotoxicity in nerve gas poisoned casualties.
Keywords: Acetilholinesteraza; Cholinesterases; Cholinesterase Inhibitors; Holinesterazni inhibitorji; Kinetika; Acetylcholinesterase; Binding Sites; Mesta vezave; Holinesteraze; Kinetics; Kemični bojni strupi; Enzyme Reactivators; Encimski reaktivatorji; Chemical Warfare Agents; encimi; struktura; delovanje; inhibicija